Potential impacts of UV exposure on lichen communities: a pilot study of Nothofagus dombeyi trunks in southernmost Chile. Issue 4 (23rd June 2015) - Trest, Marie T.; Will-Wolf, Susan; Keuler, Rachel; Shay, Nathaniel; Hill, Karen; Studer, Alyssa; Muench, Andy; Alexander, Zachary; Adams, Axel; Dittberner, Leah; Feehan, Martin; Lee, Hannah; et al.
Abstract : High‐latitude terrestrial ecosystems face the triple threats of climate warming, increased exposure to UV arising from polar ozone depletion, and deforestation. Lichen communities of southernmost Chile are recognized for their high diversity, which includes nitrogen‐fixing cyanolichens. Such lichens are common on forest trees, contribute nitrogen to forests, and are sensitive to exposure following deforestation (widespread in this region). In a pilot study of exposure effects on tree lichens, using nondestructive imaging methods, we compared lichen communities on trunks of isolated vs. forest tree trunks of southern Chilean beech ( Nothofagus dombeyi, Nothofagaceae). We chose trees of similar diameter and trunk lean angle in conserved forest and nearby logged meadow on Navarino Island, XII Region Magallanes and Chilean Antarctica, Chile, within the annual southern ozone hole. Ninety‐five percent of cyanolichen records, including Nephroma antarcticum, and 66% of records for other foliose lichens were from the forest, whereas pendulous usneoid lichens dominated N. dombeyi bark at the meadow site. Limitation of cyanolichen growth on isolated trees could affect ecosystem function in this poorly studied habitat. Possible factors contributing to strong community differences were increased light intensity, UV radiation, and wind stress, plus limited ability of lichens to colonize isolated trees in the logged meadow. UV radiation was likely an important stressor for some lichen species but not others. We recommend more extensive monitoring to pinpoint causes of differing lichen communities, and we encourage better protection of bark‐dwelling lichens in southern hemisphere regions facing multiple threats.